Lower Expression of SLC27A1 Enhances Intramuscular Fat Deposition in Chicken via Down-Regulated Fatty Acid Oxidation Mediated by CPT1A - Qiu, Fengfang; Xie, Liang; Ma, Jing-e; Luo, Wen; Zhang, Li; Chao, Zhe; Chen, Shaohao; Nie, Qinghua; Lin, Zhemin; Zhang, Xiquan (Frontiers in Physiology, 2017)
Intramuscular fat (IMF) is recognized as the predominant factor affecting meat quality due to its positive correlation with tenderness, juiciness and flavor. Chicken IMF deposition depends on the balance among lipid synthesis, transport, uptake and subsequent metabolism, involving a lot of genes and pathways, however, its precise molecular mechanisms remain poorly understood. In the present study, the breast muscle tissue of female Wenchang chickens (WC) (higher IMF content, 1.24 in D120 and 1.62 in D180) and female White Recessive Rock chickens (WRR) (lower IMF content, 0.53 in D120 and 0.90 in D180) were subjected to RNA-sequencing (RNA-seq) analysis. Results showed that many genes related to lipid catabolism, such as SLC27A1, LPL, ABCA1 and CPT1A were down-regulated in WC chickens, and these genes were involved in the PPAR signaling pathway and formed an IPA® network related to lipid metabolism. Furthermore, SLC27A1 was more down-regulated in WRR.D180.B than in WRR.D120.B. Decreased cellular triglyceride (TG) and up-regulated CPT1A were observed in the SLC27A1 overexpression QM-7 cells, and increased cellular triglyceride (TG) and down-regulated CPT1A were observed in the SLC27A1 knockdown QM-7 cells. These results suggest that lower lipid catabolism exists in WC chickens but not in WRR chickens, and lower expression of SLC27A1 facilitate IMF deposition in chicken via down-regulated fatty acid oxidation mediated by CPT1A. These findings indicate that reduced lipid catabolism, rather than increased lipid anabolism, contributes to chicken IMF deposition.